Self-Concept Disturbances As A Psychosocial Issue In Women With Breast Cancer: A Literature Review - Yuni Purwanti; Fitriani Sehuwaky; Julfanih Julfanih; Arum Ariasih (CV. AFDIFAL MAJU BERKAH, 2026)
Breast cancer is a chronic disease that causes not only physical problems but also psychosocial distress in women. Physical changes resulting from mastectomy, chemotherapy, and radiation therapy can affect patients’ self-concept through body image disturbances, decreased self-esteem, anxiety, and a crisis of feminine identity. These conditions can impact patients’ quality of life and treatment adherence. This literature review aims to analyze self-concept disturbances in women with breast cancer based on recent research. This study employed a narrative literature review method. Articles were obtained through searches on Google Scholar, PubMed, GARUDA, ScienceDirect, and Scopus using the keywords “breast cancer,” “self-concept,” “body image,” “kanker payudara,” and “konsep diri.” The articles used were full-text articles in Indonesian and English from the period 2021–2026. A total of 15 articles that met the inclusion criteria were analyzed narratively through data reduction, theme categorization, and synthesis of research results. The review findings indicate that self-concept disturbances in breast cancer patients are characterized by negative body image, reduced self-confidence, depression, anxiety, and difficulty accepting bodily changes. Influencing factors include age, psychological condition, cancer stage, family support, partner support, and social stigma. Psychosocial interventions such as counseling, support groups, and Cognitive Behavioral Therapy are effective in helping to improve patients’ self-acceptance. Disturbed self-concept is a significant psychosocial issue among women with breast cancer that affects patients’ quality of life and treatment process. A holistic, multidisciplinary, and biopsychosocial approach to healthcare is necessary to help improve the psychological adaptation and well-being of breast cancer patients.